Dopant‐Free, Donor–Acceptor‐Type Polymeric Hole‐Transporting Materials for the Perovskite Solar Cells with Power Conversion Efficiencies over 20%. Issue 5 (16th December 2019) - You, Guofeng; Zhuang, Qixin; Wang, Lijun; Lin, Xinyu; Zou, Ding; Lin, Zhenghuan; Zhen, Hongyu; Zhuang, Wenliu; Ling, Qidan
Abstract: The rich molecular design of electron donor (D)–acceptor (A) polymers offers many valuable clues to obtain high‐efficiency hole‐transporting materials (HTMs) for use in perovskite solar cells (PVSCs). The fused aromatic or heteroaromatic units can increase the conjugation of the polymer backbone to facilitate electron delocalization, which increases the rigidity of adjacent units to prevent rotational disorder and lower the reorganization energy, leading to improved carrier mobility and optimized film morphology. In this work, fused‐ring ladder‐type indacenodithiophene and indacenodithieno[3, 2‐b]thiophene are used as D units, benzodithiophene‐4, 8‐dione as the A unit, and thienothiophene as a π‐bridge to form the D–A polymers PBDTT and PBTTT, respectively. Both polymers exhibit favorable properties as HTMs including suitable energy levels, high hole mobility, and excellent film quality. Both dopant‐free HTMs endow n‐i‐p PVSCs with promising performance and stability. A maximum power conversion efficiency of 20.28% is achieved for PBDTT‐based devices, which is among the highest values reported to date. Abstract : Two electron donor (D)–electron acceptor (A)‐type polymers PBDTT and PBTTT are developed as hole‐transporting materials for perovskite solar cells (PVSCs). Both polymers endow the PVSCs promising device performance. A power conversion efficiency of 20.28% is achieved from the devices with dopant‐free PBDTT. High device stability can be expected by employing these compact and hydrophobic polymeric hole‐transporting layers.